Community perceptions of enrolment of indigents into the National Health Insurance Scheme in Ghana: a case study of the Livelihood Empowerment against Poverty Programme - Patricia Akweongo; Edmund Voetagbe; Fabrizio Tediosi; Dominic Dormenyo Gadeka; Paola Salari; Moses Aikins (BMC, 2022)
Abstract Background The Livelihood Empowerment against Poverty (LEAP) programme in Ghana as part of its beneficiary programme, identifies the poor/indigents for exemptions from premium payments in the National Health Insurance Scheme (NHIS). This paper sought to understand community perceptions of enrolling the poor in the NHIS through LEAP in order to inform policy. Methods The study adopted a descriptive cross-sectional study design by using a qualitative approach. The study was conducted in three geographical regions of Ghana: Greater Accra, Brong-Ahafo and Northern region representing the three ecological zones of Ghana between October 2017 and February 2018. The study population included community members, health workers, NHIS staff and social welfare officers/social development officers. Eighty-one in-depth interviews and 23 Focus Group Discussions were conducted across the three regions. Data were analysed thematically and verbatim quotes from participants were used to support the views of participants. Results The study shows that participants were aware of the existence of LEAP and its benefits. There was, however, a general belief that the process of LEAP had been politicized and therefore favours only people who were sympathizers of the ruling government as they got enrolled into the NHIS. Participants held the view that the process of selecting beneficiaries lacked transparency, thus, they were not satisfied with the selection process. However, the study shows the ability of the community to identify the poor. The study reports varying concepts of poverty and its identification across the three ecological zones of Ghana. Conclusion There is a general perception of politicization and lack of transparency of the selection of the poor into the NHIS through the LEAP programme in Ghana. Community-based approaches in the selection of the indigent are recommended to safeguard the NHIS-LEAP beneficiary process.